2014
DOI: 10.1016/j.wear.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and analysis of audible sound energy emissions during single point machining of HSTS with PVD TiCN cutter insert across full tool life

Abstract: In precision engineering, tool wear affects the dimensional accuracy and surface finish of machined components. Currently, errors associated with tool wear remain uncompensated for and are usually only detected at the end of the machine cycle, by which time the product may be scrap. If real-time, accurate monitoring were available, machine parameters could be adjusted to compensate for tool wear thereby minimising waste. Experienced machinists in Schivo Precision have been able to detect a poorly performing cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…One of the well-known techniques is to measure and analyze Acoustic Emission (AE) from machining operations. AE has already been employed in numerous engineering systems with the aim of fault recognition [20,14]. Guo and Ammula [19] described the basic information required in the development of applied on-line AE monitoring system to check the surface integrity in hard machining.…”
Section: Introductionmentioning
confidence: 99%
“…One of the well-known techniques is to measure and analyze Acoustic Emission (AE) from machining operations. AE has already been employed in numerous engineering systems with the aim of fault recognition [20,14]. Guo and Ammula [19] described the basic information required in the development of applied on-line AE monitoring system to check the surface integrity in hard machining.…”
Section: Introductionmentioning
confidence: 99%
“…11 Aggregate spectral difference approach is commonly used to analyze noise signals spectrum change to detect tool wear. 12 Feature extraction method based on time–frequency domain analysis and adaptive kernel principal components analysis (AKPCA) can process noise-reduced audio signals to monitor tool wear. 13 Based on decision tree (J48 algorithm) technology, Madhusudana et al used discrete wavelet transform (DWT) method to extract a set of discrete wavelet features from the noise signals of milling tool for fault diagnosis of face milling cutters.…”
Section: Introductionmentioning
confidence: 99%
“…AE techniques are exact and can be used, for example, for carrying out instrumented tests in the sliding contact stress in several processes. Downey et al [7] developed a study to determine whether it was possible to monitor and predict the cutting tool integrity using a simple audio sensor of acoustic emission. The results showed that the analysis performed had a high capability to define the tool wear.…”
Section: Introductionmentioning
confidence: 99%